Addressing transboundary cooperation in the Eastern Nile through the Water-Energy-Food Nexus: Insights from an E-survey and key informant interviews - Berga, Helen; Ringler, Claudia; Bryan, Elizabeth; ElDidi, Hagar; Elnasikh, Sara (International Food Policy Research Institute, 2017)
The Nile is the lifeblood of northeastern Africa, and its roles for and interdependency with the national economies it traverses and binds together grow as it moves from source to sea. With rapid economic development—population growth, irrigation development, rural electrification, and overall economic growth—pressures on the Nile’s water resources are growing to unprecedented levels. These drivers of change have already contributed to stark changes in the hydropolitical regime, and new forms of cooperation and cross-sectoral collaboration are needed, particularly in the Eastern Nile Basin countries of Egypt, Ethiopia, Sudan, and South Sudan. As direct sharing of water resources is hampered by unilateral developments, the need has increased for broader, cross-sectoral collaboration around the water, energy, and food sectors. This study is conducted to assess and understand the challenges of and opportunities for cooperation across the water-energy-food nexus nationally in Egypt, Ethiopia, and Sudan, as well as regionally across the Eastern Nile. To gather data, the paper uses an e-survey supplemented with key informant interviews geared toward national-level water, energy, and agriculture stakeholders, chiefly government staff and researchers. Findings from the survey tools suggest that most respondents strongly agree that collaboration across the water, energy, and agriculture sectors is essential to improve resource management in the region. At the same time, there is ample scope for improvement in collaboration across the water, energy, and food sectors nationally. Ministries of water, energy, and food were identified as the key nexus actors at national levels; these would also need to be engaged in regional cross-sectoral collaboration. Respondents also identified a wide range of desirable cross-sectoral actions and investments—both national and regional—chiefly, joint planning and operation of multipurpose infrastructure; investment in enhanced irrigation efficiency; joint rehabilitation of upstream catchments to reduce sedimentation and degradation; and investment in alternative renewable energy projects, such as wind and solar energy.